Problematika Dan Tantangan Pembelajaran Pendidikan Agama Islam Di Perguruan Tinggi Umum - Nurti Budiyanti; Asep Bahria; Uus Ruswandi; Bambang Samsul Arifin Samsul Arifin (LPPM IAI Hasanuddin Pare-Kediri, 2021)
This article aims to analyze the various problems and challenges of PAI learning in Public Universities. Higher Education is the highest level of education that has a very large role in realizing a noble Bachelor' s degree, but the reality is that there are still many students who have a person who is not commendable. It is necessary to implement appropriate strategies in dealing with the challenges of Islamic religious education in Public Universities. This research uses descriptive qualitative approach with library research method. The results showed that various problamatika of Islamic religious education is influenced by several challenges, namely challenges in the fields of politics, culture, science and technology, economics, society, and value systems. There needs to be efforts to improve the quality of Islamic education by reactivating every component in the world of education, various components that are important to be considered and improved together are (1) Curriculum Components, (2) Objective Components, (3) Material Components, (4) Strategic Components, (5) Media Components, and (6) Evaluation Components. Thus, these efforts can be made to improve the quality of Islamic education, namely by improving the components in the institution itself, in order to be able to answer the challenges that exist by not abandoning identity as an educational institution that integrates Islamic values.